The relationship of house price to the housing supply and demand in Malaysia - Redzuan, Nur Harena; Kassim, Salina (2016)
Theoretically, house prices are determined by the interaction of supply and demand in the housing market. This study aims to examine the relationship between house price to the supply side (represented by construction sector index) and demand side (represented by income level) using the ARDL cointegration test time series approaches in the context of Malaysia. It adopts the performance indicators of Malaysia housing market: Index of the Construction Sector, the real Gross Domestic Product and the House Price Index, to examine long-term and short-term correlations among these variables. The ARDL cointegration test indicates the presence of a long-run relationship between house price and housing production supply and demand side. The main significance of this study is that to address the critical gaps in the existing literature on the movement of trends in the construction sector, income level and house price index.